Pedagogical Communication Analysis in Training Scientific Articles Writing - Fauziya, Diena San; Yeti, Mulyati; Andoyo, Sastromiharjo; Dadang S., Anshori (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
This research is motivated by the importance of writing scientific articles for academics. The importance of this writing activity in the end led to the rapidly increasing of scientific article writing training in various institutions. The existence and success of the training is of course based on indicators of training implementation, one of which is the pedagogical communication strategy developed by tutors or resource persons. This is important because communication or the use of appropriate language is believed to melt the mental blocks that writers often experience. This study aims to describe the use of pedagogical communication in scientific article writing training. The research method used is descriptive qualitative with data sources in the form of pedagogical communication in scientific article writing training. The research instrument used was a word observation sheet with data collection through video observation and drawing conclusions based on interventions resulting from data analysis. Data analysis was carried out qualitatively by coding, describing and interpreting the data. The analysis indicators are based on pedagogical communication aspects, including 1) clarity, 2) fluency, 3) language systematics, 4) quality of interaction, and 5) use of written language. The result obtained is that pedagogical communication does not always have to be interactive or two-way or multi-directional, as long as the five aspects of pedagogical communication are met.